Factors associated with hypertriglyceridemia among the hill tribe people aged 30 years and over, Thailand: a cross-sectional study - Panupong Upala; Tawatchai Apidechkul; Chanyanut Wongfu; Siriyaporn Khunthason; Niwed Kullawong; Vivat Keawdounglek; Chalitar Chomchoei; Fartima Yeemard; Ratipark Tamornpark (BMC, 2021)
Abstract Background Triglycerides are lipids in the human body that are produced from the consumption of daily food and drink. However, elevated serum triglycerides, also known as hypertriglyceridemia (HTG), are key biomarkers indicating an unhealthy status and increased risks of cardiovascular diseases (CVDs) and pancreatitis. Different groups of people have different patterns and styles of cooking and different patterns of consumption, such as hill tribe people, who have their own unique culture and cooking practices. This study aimed to estimate the prevalence of and determine the factors associated with HTG among the hill tribe population in Thailand. Method A cross-sectional study was performed. Data and a-5 mL blood sample were collected from participants who were members of one of the six main hill tribes in Thailand: Akah, Lahu, Hmong, Yao, Karen, and Lisu. People who lived in 30 selected hill tribe villages and aged 30 years over were asked to participate the study. Pearson correlation and logistic regression were used to detect the correlations and determine the associations between variables, respectively, at a significant level of α = 0.05. Results A total of 2552 participants participated this study; 65.9% were females, 72.35% were aged 40-69 years, 76.7% had no education, 48.7% worked in the agricultural section, and 71.2% had an annual income of less than 50,000 baht/family. Regarding the triglyceride level, 41.7% of participants had elevated levels of serum triglyceride or HTG; 16.4% had a borderline high level, and 25.3% had a high level. After controlling for all potential confounder factors, three variables were found to be associated with elevated serum triglycerides. Those who were members of the Lahu and Hmong tribes were 1.62 times (95%CI = 1.25-2.01) and 1.63 times (95%CI = 1.23-2.16) more likely to have elevated serum triglycerides than those who were members of the Akha tribe, respectively. Those who used a high quantity of cooking oil for daily cooking were 0.73 times less likely to have an abnormal level of triglycerides than those who used a low quantity of cooking oil for daily cooking (95%CI = 0.58-0.91), and those who had a waist circumference indicating obesity were 1.28 times more likely to have an abnormal level of triglycerides than those who had a normal waist circumference (95%CI = 1.08-1.52). Conclusion Public health programs that focus on encouraging people to have regular exercise to reduce their body weight, particularly in some tribes, such as Lahu and Hmong, should be implemented.